FELINE PANLEUKOPENIA IN KITTENS: CLINICAL DETERIORATION AND PREVENTIVE MANAGEMENT IN A HOUSEHOLD CASE CLUSTER - Bradshaw, Afreen Ghania Moraiti; Widiantari, Ni Komang (Buletin Veteriner Udayana, 2026)
Feline panleukopenia virus (FPV) remains one of the most serious infectious diseases in cats, particularly in kittens, because of their immature immune systems and the rapid progression of disease after exposure. This study employed an exploratory qualitative household case study design based on caretaker observation and literature-informed analysis. It describes a household case cluster of feline panleukopenia involving eight kittens and interprets the observed clinical course in relation to veterinary literature on transmission, diagnosis, treatment, and prevention. Case information was obtained from the household caretaker’s direct observation during routine home care and from veterinary consultation after the kittens developed acute illness. The diagnosis was made by a veterinarian based on clinical examination, visible clinical signs, and the clustered progression of illness in the household setting. The observed course began with sudden weakness and refusal to eat, followed by vomiting, diarrhea, dehydration, progressive clinical deterioration, and sequential death despite prescribed medication and supportive home care. All eight affected kittens died over the following weeks, resulting in a case fatality rate of 100% in this household cluster. The shared household environment, including common living space, feeding areas, bedding, surfaces, and human handling, represented a plausible setting for repeated indirect exposure and cross-contamination. Literature-informed analysis indicates that FPV is environmentally persistent, spreads efficiently through fecal-oral and fomite transmission, and is most effectively controlled through timely vaccination, parvocidal disinfection, early isolation, and prompt veterinary management. This study highlights that once overt clinical disease develops, treatment is often supportive rather than curative. The findings emphasize the importance of prevention-oriented household management and suggest that reducing FPV-related mortality in kittens depends primarily on integrated biosecurity rather than treatment alone.